ANALYSIS OF INTEGRATED VILLAGE PLANNING TOWARDS INDEPENDENT VILLAGE IN KECAMATAN CILELES, LEBAK BANTEN DISTRICT - Alfida Aziz; Faisal Marzuki; Mahendro Sumardjo (Jurnal Ilmiah Econosains, 2021)
This research was conducted in order to participate in advancing the Cileles Lebak Banten District, the purpose of this study was to identify the problems faced by the Cileles Banten District in order to become an Independent Village so that a concrete picture would be obtained about the extent of the obstacles to being able to get to an independent village, Members of the population. from the research were the Village Heads in Cileles Lebak Banten District. This research uses qualitative analysis methods. Three villages that have been able to make plans to become independent villages, the research sample is 12 villages in the Cileles sub-district using surveys and questionnaires using Google Form.